PENDIDIKAN TENAGA PASTORAL YANG INTEGRAL DAN KONTEKSTUAL DI INDONESIA - Gunawan, Leo Agung Srie; Sihombing, Kaisar Octavianus (UNIKA Santo Thomas, 2020)
As Christians, it is our duty to tell the world the truth. The truth is not totally an abstract concept. By the existence of Jesus in time and space, we are able to know God himself empirically according to our sensibilities as human being. In short, proclaiming Jesus’ life is proclaiming the truth itself. Nowadays, this duty requires more effort in order to spread the spirituality of Jesus to more people. Progressive development in many ways and stuff bring more obstacles than before. Those who involve themselves in ecclesiastical services should improve their skills due to many challenges among plethora misleading teaching and misconception about what the truth is. In this case, church takes important part in educating and formatting certain people – they could be either priests, religious men or women, or lay people – through its ecclesiastical studies. As for progress, there are at least four fundamental elements we should to care about in order to build better and updated ecclesiastical education.